2003
DOI: 10.1007/s00213-003-1511-1
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol increases the disruptive effect of alcohol on spatial working memory in rats: a dopaminergic modulation in the medial prefrontal cortex

Abstract: These results showed that ETOH administered directly in the mPFC disrupts short- and long-term spatial working memory. The increase of the disruptive effect of ETOH produced by a dopaminergic blockage, particularly in the mPFC, suggests that the dopaminergic neurotransmission in this cortical area might modulate ETOH effects on spatial working memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The disruptive effect of Δ 9 -THC was observed at the dose of 100 μg, but not at a lower (32 μg) or higher (180 μg) dose, in a manner similar to that observed previously for alcohol administered in the mPFC (Oliveira and Nakamura-Palacios 2003). As was the case for alcohol, the lack of a disruptive effect at a higher dose (180 μg) of Δ 9 -THC IC in 1-h delayed task is also somewhat difficult to explain.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The disruptive effect of Δ 9 -THC was observed at the dose of 100 μg, but not at a lower (32 μg) or higher (180 μg) dose, in a manner similar to that observed previously for alcohol administered in the mPFC (Oliveira and Nakamura-Palacios 2003). As was the case for alcohol, the lack of a disruptive effect at a higher dose (180 μg) of Δ 9 -THC IC in 1-h delayed task is also somewhat difficult to explain.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the cognitive dysfunction induced by abused drugs may be strongly related to drug dependence and addiction, sharing neurotransmission dysfunction in same structures of the brain reward circuit, including the mPFC. In fact, studies in our laboratory showed that alcohol administered directly in the mPFC impaired shortand long-term spatial working memory (Oliveira and Nakamura-Palacios 2003).…”
Section: Introductionmentioning
confidence: 99%